Effect of aqueous phase pH on liquid–liquid extraction with impinging-jets contacting technique - Saien, Javad; Ojaghi, Sayed Ali (Journal of industrial and engineering chemistry (Seoul, Korea), 2010)
The influence of aqueous phase pH on the rate of liquid–liquid extraction was investigated using a two impinging-jets contacting device with a high velocity of jet flows. The recommended chemical system of toluene–acetone–water was employed. Applying pH values from its natural value of 5.6–8, a range in which most industrial waters are lain, for the jets colliding force within 70.3–214.6 mN, leads a reduction in extraction efficiency and overall volumetric mass transfer coefficient up to about 18.9% and 35.2% respectively. A significant high variation is observed when the aqueous phase pH exceeds the water neutral value toward alkali conditions. These variations can be attributed to the adsorption of hydroxyl ions and lowering interfacial tension. A comparison between the results in this work and those for drop dispersion extraction indicates a high sensitivity in the impinging technique. As expected, increasing jets force improves the performance of the contacting device; however, simultaneously, the retarding effect of pH would be intensified. The variation of interfacial tension with pH was obtained and with the aid of dimensionless numbers, an empirical correlation was developed for the prediction of overall volumetric mass transfer coefficient.